Incorporating placental tissue in cord blood banking for stem cell transplantation. Issue 8 (3rd August 2018) - Teofili, Luciana; Silini, Antonietta R.; Bianchi, Maria; Valentini, Caterina Giovanna; Parolini, Ornella
ABSTRACT: Introduction : Human term placenta is comprised of various tissues from which different cells can be obtained, including hematopoietic stem cells and mesenchymal stem/stromal cells (MSCs). Areas covered : This review will discuss the possibility to incorporate placental tissue cells in cord blood banking. It will discuss general features of human placenta, with a brief review of the immune cells at the fetal–maternal interface and the different cell populations isolated from placenta, with a particular focus on MSCs. It will address the question as to why placenta-derived MSCs should be banked with their hematopoietic counterparts. It will discuss clinical trials which are studying safety and efficacy of placenta tissue-derived MSCs in selected diseases, and preclinical studies which have proven their therapeutic properties in other diseases. It will discuss banking of umbilical cord blood and raise several issues for improvement, and the applications of cord blood cells in non-malignant disorders. Expert commentary : Umbilical cord blood banking saves lives worldwide. The concomitant banking of non-hematopoietic cells from placenta, which could be applied therapeutically in the future, alone or in combination to their hematopoietic counterparts, could exploit current banking processes while laying the foundation for clinical trials exploring placenta-derived cell therapies in regenerative medicine.